2012
DOI: 10.1021/bc200661w
|View full text |Cite
|
Sign up to set email alerts
|

End-Point Immobilization of Recombinant Thrombomodulin via Sortase-Mediated Ligation

Abstract: We report an enzymatic end-point modification and immobilization of recombinant human thrombomodulin (TM), a cofactor for activation of anticoagulant protein C pathway via thrombin. First, a truncated TM mutant consisting of epidermal growth factor-like domains 4–6 (TM456) with a conserved pentapeptide LPETG motif at its C-terminal was expressed and purified in E. coli. Next, the truncated TM456 derivative was site-specifically modified with N-terminal diglycine containing molecules such as biotin and the fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…There was no obvious change in PC activation activities of dual-modified conjugates by compared to unmodified TM, indicating that the one-pot double modification does not hamper the TM 456 activity. It has been reported that the activity decline of immobilized TM may be caused by random modification, [19] whereas in our previous work, [13] the activity of TM was fully retained after the site-specific functionalization and immobilization of TM via SML. Our study here further demonstrated that it is feasible to immobilize TM and introduce other functionalities at the same time without affecting its activity, which will be used in anticoagulant materials with multi-functions in the future.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…There was no obvious change in PC activation activities of dual-modified conjugates by compared to unmodified TM, indicating that the one-pot double modification does not hamper the TM 456 activity. It has been reported that the activity decline of immobilized TM may be caused by random modification, [19] whereas in our previous work, [13] the activity of TM was fully retained after the site-specific functionalization and immobilization of TM via SML. Our study here further demonstrated that it is feasible to immobilize TM and introduce other functionalities at the same time without affecting its activity, which will be used in anticoagulant materials with multi-functions in the future.…”
mentioning
confidence: 68%
“…In our previous study, we expressed a TM 456 derivative with C-terminal LPETG tag for its end-point immobilization via SML, where the activity of immobilized TM 456 was successfully retained. [13] In the present study, we designed a recombinant TM 456 derivative with azidohomoalanine for SPAAC modification and LPETG tag for the recognition of SrtA both at the C-terminal of TM 456 (TM 456 -Azide-LPETG, named as TM 456 AL) (Figure 1) (amino acid sequence see Supporting Information S1). In addition, since TM 456 contains 9 pairs of disulfide bonds, for the proper folding of recombinant protein, a DsbA together with a His tag were fused to the N-terminal of TM 456 protein (DsbA-His 6 -TM 456 AL), which was expressed in E. coli.…”
mentioning
confidence: 99%
“…invented a SrtA‐based fabrication method of TM‐modified surfaces by using diglycine covered glass slides and a truncated TM mutant that exhibits the LPETG motif. The resulting surfaces showed significant protein C activation‐promoting capabilities 96…”
Section: Immobilization Of Proteins On Artificial Surfacesmentioning
confidence: 99%
“…The resulting surfaces showed significant protein C activation-promoting capabilities. [96] Other types of modified surfaces utilized in biomedical applications include polymeric capsules, liposomes and hydrogels that can be utilized, for example, as drug-delivery vehicles. Caruso et al used the layer-by-layer technique to generate capsules consisting of alkyne-modified poly(N-vinyl pyrrolidone) and alkyne-modified PEG.…”
Section: Peptide and Protein Cyclizationmentioning
confidence: 99%
“…Recently, we reported an end‐point modification and immobilization of recombinant TM via sortase A‐mediated ligation (SML) by expression of a recombinant TMEGF456 domain with C‐terminal LPETG pentapeptide (rTMD2 4 – 6 ‐LPETG) (Fig. B) . The expression yield of recombinant TMD456 is higher than that with no unnatural amino acid used.…”
Section: Recombinant Tm Of Different Domains and Their Biological Actmentioning
confidence: 99%